Matter and consciousness : a contemporary introduction to the philosophy of mind - Churchland, Paul M. (Cambridge, Mass. ; London : MIT, 1999)
The ontological problem (the mind-body problem)
Dualism
Philosophical behaviorism
Reductive materialism (the identity theory)
Functionalism
Eliminative materialism
The semantical problem
Definition by Inner Ostension
Philosophical behaviorism
The theoretical network thesis and folk psychology
Intentionality and the propositional attitudes
The epistemological problem
The problem of other minds
The problem of self-conscious
Methodological problem
Idealism and phenomenology
Methodological behaviorism
The cognitive/computational approach
Methodological materialism
Artificial intelligence
Computers: Some elementary concepts
Programming intelligence: The piecemeal approach
Neuroscience
Neuroanatomy: The evolutionary background
Neurophysiology and neural organization
Neuropsychology
Cognitive neurobiology
AI again: Parallel distributed processing
Expanding our perspective
1. The distribution of intelligence in the universe
2. The expansion of introspective consciousness
Bibliografija iza svakog pgolavlja
Kazalo
Keywords: inteligencija; ontologija; semantika; epistemologija; idealizam; fenomenologija; metodološki biheviorizam; kognicija; metodološki materijalizam; umjetna inteligencija; neuroznanost